- #1

foo_fighter@hotmail.

Thanks.

- Thread starter foo_fighter@hotmail.
- Start date

- #1

foo_fighter@hotmail.

Thanks.

- #2

jcsd

Science Advisor

Gold Member

- 2,090

- 11

The formula is:

g = a(M_{1} + M_{2})/(M_{1}- M_{2})

using F = ma and F = mg

Gravity is acting on both the weights therefore:

F_{1} = M_{1}g

F_{2} = M_{2}g

The total force acting down is given by:

F = F_{1} - F_{2}

which is:

F = g(M_{1} - M_{2})

As the force is pulling both weights we can view the two weights as one single weight being acted on with a mass of M_{1} + M_{2}, so using F = ma

F = a(M_{1} + M_{2})

We,ve now got two terms for the same force so we can subsitue in for F:

a(M_{1} + M_{2}) = g(M_{1} - M_{2})

changing this around:

g = a(M_{1} + M_{2})/(M_{1}- M_{2})

Q.E.D.

g = a(M

using F = ma and F = mg

Gravity is acting on both the weights therefore:

F

F

The total force acting down is given by:

F = F

which is:

F = g(M

As the force is pulling both weights we can view the two weights as one single weight being acted on with a mass of M

F = a(M

We,ve now got two terms for the same force so we can subsitue in for F:

a(M

changing this around:

g = a(M

Q.E.D.

Last edited:

- Last Post

- Replies
- 9

- Views
- 2K

- Last Post

- Replies
- 9

- Views
- 5K

- Last Post

- Replies
- 4

- Views
- 3K

- Last Post

- Replies
- 3

- Views
- 1K

- Last Post

- Replies
- 8

- Views
- 3K

- Replies
- 5

- Views
- 1K

- Replies
- 1

- Views
- 3K

- Replies
- 4

- Views
- 1K

- Replies
- 11

- Views
- 7K

- Replies
- 0

- Views
- 2K